Analysis of Marchantia polymorpha–microorganism interactions: basis for understanding plant–microbe and plant–pathogen interactions - Poveda, Jorge (Frontiers in Plant Science, 2024)
Marchantia polymorpha is a bryophyte gaining significance as a model plant in evolutionary studies in recent years. This is attributed to its small-sequenced genome, standardized transformation methodology, global distribution, and easy and rapid in vitro culturing. As an evolutionary model, M. polymorpha contributes to our understanding of the evolution of plant defensive responses and the associated hormonal signaling pathways. Through its interaction with microorganisms, M. polymorpha serves as a valuable source of knowledge, yielding insights into new microbial species and bioactive compounds. Bibliographic analysis involved collecting, reading, and categorizing documents obtained from the Scopus and Web of Science databases using different search terms. The review was based on 30 articles published between 1995 and 2023, with Japanese and Spanish authors emerging as the most prolific contributors in this field. These articles have been grouped into four main themes: antimicrobial metabolites produced by M. polymorpha; identification and characterization of epiphytic, endophytic, and pathogenic microorganisms; molecular studies of the direct interaction between M. polymorpha and microorganisms; and plant transformation using bacterial vectors. This review highlights the key findings from these articles and identifies potential future research directions.